Leptin in debelost - nevroendokrini, presnovni in aterogeni učinki leptina - Šabovič, Mišo (Zdravniški vestnik, 2003)
Background. Leptin is an adipocyte-derived hormone that was recently discovered. Leptin and leptin resistance play an important role in the pathogenesis of obesity. Leptin acts by binding to specific receptors in the hypothalamus to alter the expression of several neuropeptides that regulate food intake and energy expenditure. As commonly found, obese persons have leptin resistance and consequently attenuated effects of leptin. Mechanism underlying leptin resistance has not been explained yet: it might be the result of a receptor or post receptor defect, impaired transport of leptin through cerebrovascular barrier or inactivation of leptin by binding proteins.Phase 1 and 11 clinical trials proved that recombinant leptin administration to humans is safe. First results of the current phase III clinical trials demonstrated that leptin is moderately effective in the treatment of obesity. Conclusions. Beside anti-obesity effect, leptin can haveimportant metabolic and neuroendocrine effects. It is involved in glucose metabolism and insulin secretion, pathogenesis of polymetabolic syndrome, diabetes and arterial hypertension. In addition it affects some processes of atherothrombosis. It interacts with and significantly influences hypothalamic pituitary adrenal, thyroid, sexual glands and growth hormone axes. Explaining the mechanism of leptin resistance could be important for understanding the pathogenesis of obesity and ssociated pathologic states as polymetabolic syndrom, diabetes, arterial hipertension and atherothrombosis.
Keywords: Adipociti; Adipocytes; Anoreksija nervoza; Anorexia Nervosa; Atherosclerosis; Cachexia; Debelost; Diabetes Mellitus; endokrinologija; Etiology; Hipertenzija; Hypertension; Insulin Resistance; Insulinska rezistenca; Kaheksija; leptin; Metabolism; Obesity; Secretion; Sladkorna bolezen; telesna teža; therapy; zdravljenje